Technical challenges for the optimum penetration of grid-connected photovoltaic systems: Spain as a case study. (January 2020) - Colmenar-Santos, Antonio; Linares-Mena, Ana-Rosa; Molina-Ibáñez, Enrique-Luis; Rosales-Asensio, Enrique; Borge-Diez, David
Abstract: This research reviews the technical requirements of grid-connected photovoltaic power plants to increase their competitiveness and efficiently integrate into the grid to satisfy future demand requirements and grid management challenges, focusing on Spain as a case study. The integration of distributed resources into the electric network, in particular photovoltaic energy, requires an accurate control of the system. The integration of photovoltaic energy has resulted in significant changes to the regulatory framework to ensure proper integration of distributed generation units in the grid. In this study, the requirements of the system operator for the management and smart control are first analysed and then the technical specifications established by the network operator in reference to the components of the facility are evaluated. This analysis identifies the shortcomings of the current legislation and concludes with a summary of the main technical recommendations and future regulatory challenges that need to be undertaken in the future. It is presented as a reference case that can be adapted worldwide. Graphical abstract: Image 1078 Highlights: Technical requirements of grid-connected photovoltaic power plants are reviewed. Analysis of the main technical requirements is particularized for the case of Spain. Challenges in communications, control and monitoring and metering are analysed. Technical and safety requirements for grid connection are studied. Future trends focused in smart grid PV integration are highlighted.